Advanced mechanical vibrations - Dukkipati, Rao V. ([S.l.] : Alpha Science Intl Ltd, 2006)
Discusses in a concise but through manner fundamental statement of the theory, principles and methods of mechanical vibrations. The book includes concepts and review of analytical dynamics; the basic single degree of freedom systems and the complex multiple degree of freedom systems; the energy and matrix methods; Lagrange's equations; continuous systems; Vibration measurements and control; finite element method and Nonlinear and random vibrations.